Strong and weak pulsar radio emission due to thunderstorms and raindrops of particles in the magnetosphere - Chen, X.; Yan, Y.; Han, J. L.; Wang, C.; Wang, P. F.; Jing, W. C.; Lee, K. J.; Zhang, B.; Xu, R. X.; Wang, T.; Yang, Z. L.; Su, W. Q.; et al. (Nature Astronomy, 2023)
Pulsars radiate radio signals when they rotate. However, some old pulsars often stop radiating for some periods. The underlying mechanism remains unknown, while the magnetosphere during nulling phases is hard to probe due to the absence of emission measurement. Here we report the detection and accurate polarization measurements of sporadic weak narrow dwarf pulses detected in the ordinary nulling state of pulsar B2111+46 via the Five-Hundred-Meter Aperture Spherical radio Telescope (FAST). Further analysis shows that their polarization angles follow the average polarization angle curve of normal pulses, suggesting no change of magnetic field structure in the emission region in the two emission states. Whereas radio emission of normal individual pulses is radiated by a thunderstorm of particles produced by copious discharges in regularly formed gaps, dwarf pulses are produced by one or a few raindrops of particles generated by pair production in a fragile gap of this near-death pulsar.